Isolation and Characterization of OsNAC6 cDNA from Rice (Oryza sativa L.) cv. Nipponbare, Batutegi, and Rojolele - Rachmat, Agus; Nugroho, Satya; Nurdiani, Dini; Swastika, Maria; Sukma, Dewi; Aswidinnoor, Hajrial; Sudarsono, Sudarsono (ANNALES BOGORIENSES, 2014)
Transcription factors have an important function in regulating gene expression and plant responses to stresses. The ERF, bZIP, WRKY, MYB, and NAC are stress inducible transcription factors. The OsNAC6 is a member of the NAC transcription factor family in rice and its expression is induced by abiotic stresses, wounding and blast disease. Characterization of OsNAC6 gene sequences would give a better undersanding on how OsNAC gene functions biologically. The objectives of this research are to isolate the OsNAC6 cDNA from Nipponbare, Batutegi, and Rojolele cultivars, to characterize their DNA sequences, and to compare their sequences to other NAC genes from other plants available in GenBank DNA databases. Isolated cDNA and sequencing of the fragments resulted in a 912 bp DNA sequences. Translation of the sequences yielded a protein consisted of 303 amino acid residue. Blast analysis of amino acid sequences indicated identity of isolated cDNA from three Indonesian rice cultivars are the OsNAC6 gene. Deduced amino acid residues from amplified cDNAs of Nipponbare, Batutegi, and Rojolele cultivars shared 100% sequence identities to rice OsNAC6 (Acc. # BAA89800), 71-100% sequence identity to a number of OsNAC protein from Oryza sativa and 63-83% sequence identity to NAC protein from other plants.